ANALISIS TOKOH PADA NOVEL “KUTINGGALKAN DIA KARENA DIA” KARYA DUNIA JILBAB DAN UMMU RUMAISHA - Sukriyani Sukriyani (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2022)
This research is to find out the characters in the novel I leave him because he is the work of the hijab world and ummu rumaisha. This study uses a qualitative method. Data analysis techniques (a) The researcher analyzes the characters and characterizations in the novel Kutenggahan him because he is (b) The researcher forms the building blocks associated with the characterizations in the novel Kutenggalnya because he is the work of the hijab world and ummu rumaisha. The results of this study presented some of the data obtained as evidence of research results. The data presented in this section is the data that contains the characters and as one of the elements forming the novel. Judging from the roles of the characters in the development of the story, they are distinguished into characters in the novel and additional characters, while when viewed from the function of appearance, the characters can be classified into protagonists (characters we admire), and antagonists (characters who cause conflict).